Queer Critical Intersections with Ecology and Religion. Review of Bauman, W. A. (Ed.) (2018). Meaningful Flesh: Reflections on Religion and Nature for a Queer Planet. Goleta, California: Punctum Books - Ibarra Cordero, Andrés (2021)
Fil: Ibarra Cordero, Andrés. Universiteit van Amsterdam.